Deletion of pagL and arnT genes involved in LPS structure and charge modulation in the Salmonella genome confer reduced endotoxicity and retained efficient protection against wild-type Salmonella Gallinarum challenge in chicken - Ram Prasad Aganja; Jun Kwon; Amal Senevirathne; John Hwa Lee (Veterinary Research)
Abstract Fowl typhoid (FT) poses a significant threat to the poultry industry and can cause substantial economic losses, especially in developing regions. Caused by Salmonella Gallinarum (SG), vaccination can prevent FT. However, existing vaccines, like the SG9R strain, have limitations, including residual virulence and potential reversion of pathogenicity. This study aims to develop safer and more effective SG vaccine strains through targeted genetic modifications, focusing on genes involved in lipopolysaccharide (LPS) biosynthesis and modification. We evaluated two novel mutant SG strains, JOL3015 and JOL3016, carrying in-frame deletions in ΔlonΔrfaLΔarnT and ΔlonΔrfaLΔpagL, respectively. Intramuscular immunisation of 4-week-old young birds with JOL3015 and JOL3016 strains showed minimal impact on their growth. However, the immunisation significantly increased antigen-specific IgY, sIgA secretion, and CD4+ and CD8+ T-cell responses while inducing lower pro-inflammatory cytokine levels than SG9R. Histopathological evaluations revealed substantial protection in the immunised birds, with minimal tissue damage and inflammatory responses, thus reducing the in vivo bacterial burden. Furthermore, none of the immunised birds died. This outcome highlights the significant safety and protection the selected genetic modifications conferred. Our results indicate that JOL3016 provided comparable protective outcomes on par with SG9R, yet with significantly lower endotoxicity responses during the lethal challenge with SG WT JOL422. The novel detoxified SG strains, particularly JOL3016, offer a promising alternative to existing vaccines for FT. They provide effective protection with minimal impact on poultry growth, thereby minimising the risks associated with reversion and endotoxicity. The study highlights the potential of genetically engineered vaccine strains in improving poultry health and productivity, emphasising the importance of continued research.